Cadrage, décadrage et recadrage dans Baa Baa Black Sheep : A Jungle Tale de David Malouf et Michael Berkeley - Jean-Philippe Heberlé (Revue LISA)
This article discusses Michael Berkeley’s first opera, Baa Baa Black Sheep: A Jungle Tale. Premiered under the baton of Paul Daniel on July 3rd 1993 at the Cheltenham International Festival of Music, this opera is based on two texts by Rudyard Kipling: The Jungle Books (1894-1895) and “Baa, Baa, Black Sheep” from the short story collection Wee Willie Winkie and Other Stories, first published in 1888. The libretto was penned by the Australian poet, novelist, playwright and librettist, David Malouf. After a brief survey of some of the earliest transpositions of The Jungle Books, I analyse the way David Malouf deals with both texts. “Baa Baa Black Sheep” is used as the central element of his libretto, and episodes and characters from The Jungle Books are incorporated to draw parallelism between the main topics of the two texts. Both Malouf’s endeavour and Berkeley’s, through the music, aims at deconstructing the preposterous oldest transpositions of The Jungle Books and at focusing on the key elements of Kipling’s famous book, notably identity and hybridism, two important themes of colonial and postcolonial literature. The aim of David Malouf and Michael Berkeley is to address an adult audience and show that The Jungle Books are not only aimed at children as Disney’s or Baden Powell’s appropriations of the work could wrongly make us believe.